Diffusional behavior and guest conformational analysis of hexadecane-1,16-diol and hexadecane in urea crystal model via molecular dynamics simulation approach - Mustafa, S. F. Z. (Springer Verlag, 2016)
Diffusion at the atomic or molecular level is a source of many physical, chemical, and biological processes taking place in plentiful materials. This work is an endeavor toward investigating the diffusional behavior of two different type of guests, hexadecane-1,16-diol and hexadecane enclathration in urea tunnel architecture, whereby the correlation of the diffusion mechanism with the guest’s structural and conformational properties is explored. To carry out this study, molecular dynamics simulation approach is adopted. It is found that hexadecane-1,16-diol exhibit slower diffusion with an average diffusion coefficient value ~ 1.83 × 10 - 10, where hexadecane diffuse more rapidly with an average diffusion coefficient value ~ 2.58 × 10 - 9. It is also observed that the structural properties influence the guest’s travel distance and torsion angle distribution of the trans and gauche conformational proportion. Furthermore, the observed high energy barrier accounted for hexadecane-1,16-diol and low energy barrier for hexadecane along urea tunnel systems was analyzed. The comparison of our obtained results are in close agreement with the available experimental measurements, i.e., gauche proportion properties between two different guest molecules correlate well with Raman spectroscopy investigation on α,ω-dihalogenoalkane/urea inclusion compounds. Our calculations also successfully endorse the structure-property relation between the two systems.